If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5x + -3) + 11 = -3 Reorder the terms: 5(-3 + 5x) + 11 = -3 (-3 * 5 + 5x * 5) + 11 = -3 (-15 + 25x) + 11 = -3 Reorder the terms: -15 + 11 + 25x = -3 Combine like terms: -15 + 11 = -4 -4 + 25x = -3 Solving -4 + 25x = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 25x = -3 + 4 Combine like terms: -4 + 4 = 0 0 + 25x = -3 + 4 25x = -3 + 4 Combine like terms: -3 + 4 = 1 25x = 1 Divide each side by '25'. x = 0.04 Simplifying x = 0.04
| 15w^2-1w-2=0 | | 0.5(x+100)+1.3x=131 | | (-7/3u-9)-4=(-8/u-3) | | x^2/10+x+2/3=0 | | 0.6x+8.1=7.2 | | 5x-3-4x-10=27 | | 2+2x/7+5-x/5+48/35 | | 3x^9-15x^8=9x^7 | | X^2-12X-676=0 | | 5(5x-3)+11=3 | | -2[5(x-2)-10]=80 | | 0.25x^2-1/2x=1 | | 2x+3-5=-3 | | 18-(3x+5)=8 | | 10(a-1)-2(a+2)+3=13 | | 9(4-y)+2=-2(y-4)-3 | | 8x-1+4=6 | | .16(y-1)+.06y=.18y-.3 | | 7-6x/4 | | 7-4/x | | 5x-y=100 | | .75x+.05(20-x)=.10(-46) | | x^2+16=64 | | 4p+7=12+3p | | 7.6x+3=6.6x | | r=51-2r | | (4x+5)(3y-7)= | | 6(4-3)-5(4+2)=8 | | x^2-5x=2x^2+x | | 6x+3.9=53.1 | | (x^3+11x^2+18x)/(x^2-6x-16) | | .06x+.03(6000-x)=219 |